Evaluation of the antifungal activity of extracts of the genus piper against Moniliophthora roreri, causal agent of moniliasis in cocoa - Reyes-Sanabria, Nataly A.; Rodríguez-Bocanegra, María X.; Ladino-Várgaz, Cristobal; Patiño-Ladino, Oscar J; Viviana Bogotá, Natalia; Prieto-Rodríguez, Juliet A. (Revista Productos Naturales, 2022)
Cacao (Theobroma cacao) is one of the agricultural products produced in the country and of greater economic projection due to its high demand and quality.